Interactive Effects of Body Weight and Body Condition Score on Enteric Methane Emissions in Grazing Beef Cows - Carlee M. Salisbury (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: To evaluate how body weight and body condition score, both independently and interactively, influence enteric methane production and emission efficiency in beef cows during spring grazing. Study Description: This retrospective analysis used data from a supplementation trial with mature, spring-calving beef cows grazing native pasture. Cows were weighed and scored monthly. Methane emissions were measured using GreenFeed systems (AHCS; C-Lock Inc., Rapid City, SD), and supplement intake was recorded with automated feeders. Cows were grouped by changes in body condition score over time. The Bottom Line: Cows with moderate weight and stable body condition emitted less methane per unit of supplement intake, supporting both environmental and production efficiency goals.
Keywords: methane; body weight; condition